Rút gọn biểu thức: N=(a^2+b^2+c^2)/(a-b)^2+(b-c)^2+(c-a)^2 . Cho a+b+c=0

Question

Rút gọn biểu thức:
N=(a^2+b^2+c^2)/(a-b)^2+(b-c)^2+(c-a)^2 . Cho a+b+c=0

in progress 0
Ruby 2 tháng 2021-07-27T08:59:18+00:00 2 Answers 14 views 0

Answers ( )

    0
    2021-07-27T09:00:58+00:00

    Đáp án:

    $N = \dfrac{1}{3}$

    Giải thích các bước giải:

    $\begin{array}{l}a + b + c = 0\\ \Rightarrow (a + b + c)^2 = 0\\ \Leftrightarrow a^2 + b^2 + c^2 + 2(ab + bc + ca) = 0\\ \Leftrightarrow a^2 +b^2 + c^2 = – 2(ab + bc + ca)\\ Ta\,\,được:\\ N = \dfrac{a^2 + b^2 + c^2}{(a -b)^2 + (b-c)^2 + (c-a)^2}\\ = \dfrac{a^2 + b^2 + c^2}{2(a^2 + b^2 + c^2) – 2(ab + bc + ca)}\\ = \dfrac{a^2 + b^2 + c^2}{2(a^2 + b^2 + c^2) + a^2 +b^2 + c^2}\\ = \dfrac{1}{3}\end{array}$

    0
    2021-07-27T09:01:05+00:00

    Đáp án:

     \(N=\dfrac 13\)

    Giải thích các bước giải:

    `N=(a^2+b^2+c^2)/((a-b)^2+(b-c)^2+(c-a)^2)=((a+b+c)^2-2(ab+bc+ca))/(a^2+b^2-2ab+b^2+c^2-2bc+c^2+a^2-2ac)=((a+b+c)^2-2(ab+bc+ca))/(2a^2+2b^2+2c^2-2ab-2bc-2ac)=((a+b+c)^2-2(ab+bc+ca))/(2(a^2+b^2+c^2+2ab+2bc+2ca)-6ab-6bc-6ca)=(-2(ab+bc+ca))/(-6(ab+bc+ca))=1/3`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )